The status and distribution characteristics of residual mulching film in Xinjiang, China - ZHANG, Dan; LIU, Hong-bin; HU, Wan-li; QIN, Xiao-hui; MA, Xing-wang; YAN, Chang-rong; WANG, Hong-yuan (Journal of Integrative Agriculture, 2016)
Pollution of residual plastic film in arable lands is a severe problem in China. In this study, the status of residual film and influential factors were investigated using the methods of farm survey in combination with questionnaires and quadrat sampling at a large number of field sites in Xinjiang Uygur Autonomous Region, China. The results showed that the amount of film utilization increased largely and reached to 1.8×10~5 t in 2013. Similarly, the mulching area also substantially increased in recent decades, and reached to 2.7×10~5 ha in the same year. According to the current survey, 60.7% of the sites presented a greater mulch residue than the national film residue standard（75 kg ha~（–1））, and the maximum residual amount reached 502.2 kg ha~（–1） in Turpan, Xinjiang. The film thickness, the mulching time and the crop type all influenced mulch residue. The thickness of the film had significantly negative correlation with the amount of residual film（P0.05）, while the mulching years had significantly positive correlation with it（P0.05）. The total amount of residual film in Xinjiang was 3.43×105 t in 2011, which accounted for 15.3% of the cumulative dosage of mulching. Among all the crops, the cotton fields had the largest residual amount of mulch film（158.4 kg ha~（–1））, and also the largest contribution（2.6×10~5 tons） to the total amount of residual film in Xinjiang.